Ketika Fakta Bukanlah Kebenaran: Peran Media Daring dalam Amplifikasi Misinformasi Kesehatan di Era Pandemi Covid-19 - Rani Prita Prabawangi; Megasari Noer Fatanti (Jurnal Komunikasi, 2023)
During the Covid-19 epidemic, people must not only escape getting infected with the virus, but also avoid being targeted by hoaxes. In cyberspace, there are several topics of misinformation ranging from conspiracy theories to claims of finding anti-corona medications. Various studies have discovered that during a pandemic, social media is the mechanism through which health misinformation begins and spreads. However, there is a lack of data on misinformation disseminated by other media, particularly verified media. This study intends to bridge a research gap by investigating more into how claims of traditional medicine healing Covid-19 are publicized by Indonesian online news outlets. This study did a content analysis of 14 media articles from various online media about anti-corona herbal remedies affiliated to the 'Covid-19 Herbal Research Team for the Nation.' The study's findings suggest that in reporting on anti-corona medications, the majority of the media have abandoned the discipline of verification in the news production process. The media has amplified the lies of the 'Covid-19 Herbal Research Team for the Nation' through misleading headlines and reports that only feature sole claims.